Identifying psychological difficulties in college athletes - Sutcliffe, J. H.; Greenberger, P. A. (The Journal of Allergy and Clinical Immunology, 2020)
Psychological conditions occur frequently in college students. One contributing factor is the onset of most mental health disorders occurring in late adolescence and early adulthood, as well as the identity formation and individuation that is typical of this developmental stage. Precollege trauma (emotional, physical, sexual, and witness to violence) and lower socioeconomic status can set the stage for psychological difficulties. Some of many stressors that may affect college athletes include peer pressures, independence, need to please family, friends, and coaches, high level of expectations with a very strong commitment to succeeding and winning in competitive and intense intercollegiate sports, time management for academic demands, sports, relationships, and well-being, mood status, history of mental illness, injuries including concussions, and adjusting to the length of time for recovery from injuries, fears of reinjury, or return-to-play concerns, managing body and weight concerns related to performance, and unexpected medical conditions such as infectious mononucleosis. A case is presented of a patient who is a college student-athlete with mild intermittent asthma and seasonal allergic rhinitis who was found to have generalized anxiety, surreptitious cannabis use, and bulimic symptoms. He was angry at his position coach because of lack of playing time.